Middlemarch : a study of provincial life - Eliot, George, 1819-1880 (London : Vintage Books, 2007)
Dorothea is bright, beautiful and rebellious and has married the wrong man. Lydgate is the ambitious new doctor in town and has married the wrong woman. Both of them long to make a difference in the world. But their stories bo not proceed as expected... -- back cover.
Keywords: City and town life -- Fiction; Married people -- Fiction; Young women -- Fiction